Delayed cardiac tamponade 8 months after pulmonary vein isolation. Issue 1 (July 2017) - Yamanaka, Tetsuo; Fukatsu, Toru; Kamon, Tatsuya; Kitahara, Satoshi; Ichinohe, Yoshimaro; Komatsu, Hirotaka; Hirata, Yasunobu
Abstract: We herein report the case of a 55 year-old male who underwent pulmonary vein isolation (PVI) for paroxysmal atrial fibrillation. From 8 months after PVI, exertional dyspnea rapidly appeared. When he was referred to our hospital, massive pericardial effusion was observed by transthoracic echography. The pericardiocentesis revealed bloody pericardial effusion, and improved symptoms. Although aortic dissection, autoimmune disease, infection, metastatic pericardial tumor, primary pericardial tumor, and malignant neoplasm were considered as differential diagnosis, the cause of pericardial effusion failed to be found. From these findings, the cause of hemorrhagic pericardial effusion was considered delayed cardiac tamponade induced by PVI performed 8 months earlier. <Learning objective: Cardiac tamponade occurring after pulmonary vein isolation (PVI) procedure called delayed cardiac tamponade (DCT) is not widely recognized. However, mortality from DCT is far less than 5%, and we believe that it is a complication that requires due care. This report describes that DCT can occur even after 8 months of PVI.>